2021
DOI: 10.1111/nph.17342
|View full text |Cite
|
Sign up to set email alerts
|

STARCH SYNTHASE 4 is required for normal starch granule initiation in amyloplasts of wheat endosperm

Abstract: Starch granule initiation is poorly understood at the molecular level. The glucosyltransferase, STARCH SYNTHASE 4 (SS4), plays a central role in granule initiation in Arabidopsis leaves, but its function in cereal endosperms is unknown. We investigated the role of SS4 in wheat, which has a distinct spatiotemporal pattern of granule initiation during grain development.(2) We generated TILLING mutants in tetraploid wheat (Triticum turgidum) that are defective in both SS4 homoeologs. The morphology of endosperm s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 66 publications
4
30
0
Order By: Relevance
“…To compare the role of PTST2 in leaves of different grass species, we obtained mutants defective in PTST2 orthologues of barley ( Hordeum vulgare ; Hv ), durum wheat ( Triticum turgidum ; Tt ), and Brachypodium distachyon ( Bd ). The barley ( Hvflo6 ) and wheat mutants ( Ttbgc1 ) are those described in Saito et al (2018) and Hawkins et al (2021) , respectively, whereas the Brachypodium Bdptst2 mutant carrying an insertion in exon 1 was isolated from a T-DNA mutant collection ( Supplementary Fig. S1A–C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To compare the role of PTST2 in leaves of different grass species, we obtained mutants defective in PTST2 orthologues of barley ( Hordeum vulgare ; Hv ), durum wheat ( Triticum turgidum ; Tt ), and Brachypodium distachyon ( Bd ). The barley ( Hvflo6 ) and wheat mutants ( Ttbgc1 ) are those described in Saito et al (2018) and Hawkins et al (2021) , respectively, whereas the Brachypodium Bdptst2 mutant carrying an insertion in exon 1 was isolated from a T-DNA mutant collection ( Supplementary Fig. S1A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Although PTST2 is required for normal granule initiation in the endosperm of wheat and barley ( Chia et al , 2020 ; Hawkins et al , 2021 ), its role in leaves has not yet been explored. In our study, Hvflo6 and Ttbgc1 mutants had distinct starch phenotypes in the leaves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gradually decreasing the expression of SBEs can lead to the formation of various heterogeneous starch granules, including polygonal, aggregate, elongated, and hollow granules ( Wang et al., 2018 ). Studies in wheat indicated that SSIV and BGC1 are required for proper granule initiation, as TaSSIVb-D mutation led to a decrease in starch granules per chloroplast ( Guo et al., 2017 ), and mutation of either SSIV or BGC1 resulted in multiple initiations of amyloplasts and the formation of compound granules ( Hawkins et al., 2021 ). Mutation of SSIVb (SSIV-2) or SSIIIa did not show even a slight effect on starch granule morphology in the rice endosperm, but their combination resulted in small and spherical starch granules ( Toyosawa et al., 2016 ).…”
Section: Starch Biosynthesis Pathway In Cereal Endospermsmentioning
confidence: 99%